AMRTA-X: Grasp Kinematic Analysis during Myoelectric Prehension Orthosis and Body Powered Prehension Orthosis's Usage on Brachial Plexus Injury Patients - Fundhi, Khrisna Adi Pinardi; Andriana, RA Meisy; Masduchi, Reni H; Pawana, IP Alit (Folia Medica Indonesiana, 2021)
Brachial Plexus Injury (BPI) results in decreased motor function in upper extremity and leads to reduced hand grasping movement. Orthotic prehension is designed to create artificial grasp movements in paralyzed hand. This study was to compare grasp kinematic improvement between body powered and myoelectric prehension orthosis usage in patients with BPI. This study was a single group without control and post test with experimental study. The subjects of the study (n = 11) were brachial plexus injury patients with non-functional hand strength. Joint motion and angular velocity of metacarpophalangeal (MCP) and proximal interphalangeal (PIP) joint of index finger were evaluated. There was an improvement in joint motion and angular velocity after both orthosis usage. Joint motion in MCP and PIP, Angular velocity in MCP were not significantly different between myoelectric and body powered and myoelectric prehension orthosis usage. PIP angular velocity improvement were better after body powered prehension orthosis usage (p= 0.03).In conclusion, body powered and myolectric prehension orthosis usage improved kinematic parameter of index finger's MCP and PIP joint. PIP angular velocity was better after body powered prehension orthosis usage.